The influence of Al-Ghazzali in the Malay world: translations and adaptation of his works into Jawi - Moris, Megawati (IIUM Press, 2011)
In the past, and until today, AbË ×Émid al-GhazzÉlÊ‘s writings (d. 505/1111) have left a great impact on scholars in the Malay World. For Malay-Muslims his teachings provide true Islamic knowledge and guidance to right action. This article presents selected Jawi works, written by four scholars, which are translations and adaptations of al-GhazzÉlÊ’s basic works on Sufism written during the period 1700-1900. These works are considered as agents of transmission and dissemination of al-GhazzÉlÊ’s teachings to Muslims in the Malay World who mostly do not understand Arabic. In the renditions of the original works, the Malay scholars have incorporated on what are obligatory (farÌ ‘ayn) in jurisprudence (fiqh), principles of religion (uÎËl al-dÊn) and Sufism (taÎawwuf) and they included their own commentaries as well as other scholars’ works besides al-GhazzÉlÊ’s. Nonetheless, the contents were in accordance with al-GhazzÉlÊ’s original teachings and additions were always interpreted within al-GhazzÉlÊ’s spiritual and theological frameworks. These works have indicated that the Malay scholars were not just translators but were also creative interpreters and transmitters of al-GhazzÉlÊ’s teachings.